PENGARUH PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP MENGONSUMSI TABLET TAMBAH DARAH - Muhammad Azra Inan Abdillah; Triawanti Triawanti; Azma Rosida; Meitria Syahadatina Noor; Noor Muthmainah (Homeostasis, 2022)
Iron supplementation tablets (TTD) are dietary supplements containing iron that can be given to adolescent girls to prevent iron deficiency anemia (ADB). Although the administration of TTD in adolescent girls has been implemented, the lack of knowledge and unsupportive attitude toward consuming TTD in adolescent girls can reduce the effectiveness on preventing ADB. This study aims to determine the effect of health education on knowledge and attitude of consuming TTD, a review of adolescent girls at SMP Negeri 25 Banjarmasin. Quasi-experimental research method with one-group pretest-posttest design. The research subjects were 30 people with random sampling technique. Data collection techniques using knowledge and attitude questionnaires. The analysis using the Wilcoxon Signed Ranks test showed that there was a significant difference between knowledge (p=0.00) and attitude (p=0.019) before and after health education for adolescent girls. In conclusion, health education can increase the knowledge and attitude of consuming TTD in adolescent girls